Suggestions pour la recherche en sociologie de la religion aux Etats-Unis - Schreuder, Osmund (Social compass, 1962)
The fact that religion has not tended to disappear in the United States, as certain theories predicted, but on the contrary seems to be undergoing a revival, forces us to view it as something other than a type of cultural lag. Hence the ever increasing attention accorded to the religious phenomenon by American sociologists. The explanations advanced refer to the global structure and to the particular dynamics of American society. The author here studies several hypotheses connected with these explanations, and makes a distinction between religion as practised and the religious institution itself, with the direct and indirect influence it exercises.